Basic electricity. A Text-Lab manual - ZBAR, Paul B (McGraw - Hill Book Company, 1991)
Designed for use in traditional DC/AC courses, this text serves equally well as a stand-alone introductory text and lab manual or as a lab manual for use with any basic theory text. The content of this text/lab manual is prepared with the technical assistance of the Electronic Industries Association, guaranteeing that the material is consistent with the competencies of the electronics manufacturing and service industries.